Genital herpes - Penello, Angelo M.; Campos, Bianca C.; Simão, Marcela S.; Gonçalves, Michelle A.; Souza, Pedro M.T.; Salles, Roberto S.; Pellegrini, Edilberto (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Genital herpes is an infectious disease subject to recurrent crises, with the etiologic agent of two different strains of herpes simplex virus (HSV), the type 1 (HSV-1) and type 2 (HSV-2). The vast majority of genital herpes cases is caused by HSV-2, although the prevalence of HSV-1 is on the rise, especially in young population and due to oral sex. The clinical manifestations may be primary or recurrent, the latter going on viral reactivation. The diagnosis is made by the clinical characteristics associated with laboratory confirmation of infection. Several epidemiological and clinical studies demonstrate the synergy between genital herpes and aids. In pregnancy, the major concern about HSV infection refers to the morbidity and mortality associated with neonatal infection. Currently, there is no treatment capable of curing genital herpes, but some antiviral drugs are able to decrease the duration of the disease and prevent flares. Most efforts to combat genital herpes infection are focused on vaccine development.